2013
DOI: 10.4081/mrm.2013.478
|View full text |Cite
|
Sign up to set email alerts
|

Advanced age and apnea-hypopnea index predict subclinical atherosclerosis in patients with obstructive sleep apnea syndrome

Abstract: Background: Both obstructive sleep apnea syndrome (OSAS) and coronary artery calcification (CAC) are considered to be related with the presence of coronary artery disease (CAD). In this study we evaluate the association between OSAS and presence of subclinical atherosclerosis assessed by tomographic coronary calcium score in patients who had OSAS but no history of known CAD. Methods: Seventy-three patients who were asymptomatic for CAD and had suspected OSAS were referred to overnight attended polysomnography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
2
12
0
1
Order By: Relevance
“…La inflamación e hipoxia intermitente desempeña un rol importante en el desarrollo de ateroesclerosis [14]. Al ser expuesto el endotelio a hipoxia intermitente, este activa selectivamente vías inflamatorias vasculares que promueven la formación de radicales libres de oxígeno y causan un efecto deletéreo sobre células endoteliales, macrófagos y plaquetas que posteriormente expresarán moléculas de adhesión y liberarán citocinas proinflamatorias y factores de crecimiento causando disfunción endotelial [15][16][17][18][19].…”
Section: Consecuencias Del Sahosunclassified
“…La inflamación e hipoxia intermitente desempeña un rol importante en el desarrollo de ateroesclerosis [14]. Al ser expuesto el endotelio a hipoxia intermitente, este activa selectivamente vías inflamatorias vasculares que promueven la formación de radicales libres de oxígeno y causan un efecto deletéreo sobre células endoteliales, macrófagos y plaquetas que posteriormente expresarán moléculas de adhesión y liberarán citocinas proinflamatorias y factores de crecimiento causando disfunción endotelial [15][16][17][18][19].…”
Section: Consecuencias Del Sahosunclassified
“…Several studies have investigated CAD in OSA using computed tomography (Arik et al., ; Kent et al., ; Kim et al., ; Kwon et al., ; Lutsey et al., ; Luyster, Kip, Aiyer, Reis, & Strollo, ; Matthews et al., ; Medeiros et al., ; Murphy et al., ; Nakanishi‐Minami et al., ; Pusuroglu et al., ; Seo et al., ; Sharma et al., ; Sorajja et al., ; Weinreich et al., ). However, there were considerable differences in the studied populations and diagnostic tests.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were considerable differences in the studied populations and diagnostic tests. Particularly, most studies used only coronary artery calcium score (CAC) to evaluate the severity of CAD (Arik et al., ; Kim et al., ; Kwon et al., ; Lutsey et al., ; Luyster et al., ; Matthews et al., ; Medeiros et al., ; Seo et al., ; Sorajja et al., ; Weinreich et al., ). However, recent studies demonstrated that coronary plaques are typically non‐calcified or partially calcified in OSA (Murphy et al., ; Sharma et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study, 3 our findings suggest that in patients with moderate or severe OSA syndrome, physicians should be alert for the presence of subclinical atherosclerosis. In this study, we investigated 73 patients who were asymptomatic for coronary artery disease and suspected OSA syndrome.…”
mentioning
confidence: 50%